2014
DOI: 10.1088/0953-2048/27/6/065019
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of the trapped field in MgB2bulk disks magnetized by field cooling

Abstract: We performed a numerical simulation of the trapped field properties of MgB 2 bulk disks with different superconducting characteristics magnetized by field cooling. The temperature dependence of the trapped field B T () z , and the time dependence of the local field B t () z and temperature T (t) were calculated, and compared with experimental results. Since the measured critical current density J T B (,) c was used in the simulation, the results of the simulation reproduce the experimental results well. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 18 publications
5
40
0
Order By: Relevance
“…The significant feature of the HIP#22 bulk is a small aspect ratio (d/t B ); that is, the HIP#22 is cylindrical rather than disk-shaped. The result is not supported by the numerical simulation for FCM [16], where the B z value slightly increases with increasing diameter (d) of the bulk, but is almost independent of the thickness (t B ). Increasing the t B and d values is not necessarily an effective solution to enhance the B z value.…”
Section: Methodsmentioning
confidence: 60%
“…The significant feature of the HIP#22 bulk is a small aspect ratio (d/t B ); that is, the HIP#22 is cylindrical rather than disk-shaped. The result is not supported by the numerical simulation for FCM [16], where the B z value slightly increases with increasing diameter (d) of the bulk, but is almost independent of the thickness (t B ). Increasing the t B and d values is not necessarily an effective solution to enhance the B z value.…”
Section: Methodsmentioning
confidence: 60%
“…Therefore, the trapped magnetic field of MgB 2 bulk magnet has been analyzed by the numerical calculation using finite element method (FEM). And it has been shown that the calculated result by FEM agrees well with experimental data [5]. In this calculation by FEM, they took into account of both electromagnetic and thermal equations for field-cooled magnetization (FCM) [5].…”
Section: Introductionmentioning
confidence: 65%
“…And it has been shown that the calculated result by FEM agrees well with experimental data [5]. In this calculation by FEM, they took into account of both electromagnetic and thermal equations for field-cooled magnetization (FCM) [5]. Hence, the calculation by FEM is relatively complicate.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations